Adverse Selection in the Children's Health Insurance Program - Michael A. Morrisey PhD; Justin Blackburn PhD; David J. Becker PhD; Bisakha Sen PhD; Meredith L. Kilgore RN, MSPH, PhD; Cathy Caldwell MPH; Nir Menachemi PhD (SAGE Publishing, 2015)
This study investigates whether new enrollees in the Alabama Children's Health Insurance Program have different claims experience from renewing enrollees who do not have a lapse in coverage and from continuing enrollees. The analysis compared health services utilization in the first month of enrollment for new enrollees (who had not been in the program for at least 12 months) with utilization among continuing enrollees. A second analysis compared first-month utilization of those who renew immediately with those who waited at least 2 months to renew. A 2-part model estimated the probability of usage and then the extent of usage conditional on any utilization. Claims data for 826 866 child-years over the period from 1999 to 2012 were used. New enrollees annually constituted a stable 40% share of participants. Among those enrolled in the program, 13.5% renewed on time and 86.5% of enrollees were late to renew their enrollment. In the multivariate 2-part models, controlling for age, gender, race, income eligibility category, and year, new enrollees had overall first-month claims experience that was nearly $29 less than continuing enrollees. This was driven by lower ambulatory use. Late renewals had overall first-month claims experience that was $10 less than immediate renewals. However, controlling for the presence of chronic health conditions, there was no statistically meaningful difference in the first-month claims experience of late and early renewals. Thus, differences in claims experience between new and continuing enrollees and between early and late renewals are small, with greater spending found among continuing and early renewing participants. Higher claims experience by early renewals is attributable to having chronic health conditions.